Allah versus Setan Laplace: Sebuah Usulan Konsep Tindakan Ilahi Khusus yang Trinitarian, Kovenantal dan Saintifik - Alinurdin, David (Veritas : Jurnal Teologi dan Pelayanan, 2020)
God versus Laplace’s Demon: A Proposal for Trinitarian, Covenantal and Scientific Special Divine Action Concept. In the last decade, the interaction between science and theology in the effort to develop the concept of divine action in the natural world has come to a conclusion to find a causal joint where transcendent and nonphysical Creator God can act in natural processes that occur in the world of creation. An academic movement whose credibility has been recognized in its efforts to find a causal joint in new ways that incorporate philosophical interpretations of contemporary science into theology is the Divine Action Project (DAP), which formulates a concept of divine action called NIODA (Noninterventionist Objective Divine Action). NIODA seeks to find a locus of special divine action that does not conflict with laws of nature in physical processes that can be interpreted as ontological indeterminism, such as quantum mechanics. This paper will examine the philosophical assumptions behind NIODA and show that this concept is scientifically acceptable but not theologically adequate because it is still bound by Laplace's assumption of the enlightenment's legacy which considers the universe to be causally closed to divine action. Therefore, in the last part, this paper will also propose several important points in the effort to develop a concept of special divine action that is both theologically and scientifically adequate, built on the basis of a trinitarian and covenantal biblical theology of creation.